"It's been a good time to reflect on…who isn't worth keeping around": COVID-19, adolescent relationship maintenance and implications for health education. Issue 1 (15th July 2021) - Goldstein, Alanna; Flicker, Sarah
Abstract : Purpose: This paper adds to the growing body of research examining the impacts of COVID-19 physical distancing measures on the everyday lives of young people. It draws on theories of "digital intimacies" and "relationship maintenance" to argue that young people's reflections on COVID-19, physical distancing and online relationships expose larger gaps in sex, relationships and health education pedagogies. Design/methodology/approach: Five semi-structured online focus groups were conducted with Canadian adolescents aged 16–19 probing their experiences of dating and platonic relationships during COVID-19. Narrative thematic analysis methods were used to develop themes outlining how physical distancing measures have affected young people's relationship norms, expectations and values. Findings: COVID-19 physical distancing measures and school closures appeared to create the conditions for some young people to productively reflect on the labor involved in the maintenance of their relationships in relation to considerations of proximity, reciprocity and distance. This labor was particularly articulated by female participants, many of whom expressed that life disruptions caused by COVID-19 catalyzed learning about their own relationship needs, desires and boundaries. Research limitations/implications: Results from this research are not widely generalizable, as each participant had a unique experience with COVID-19 physical distancing measures, schooling and in-person contact. Due to anonymity measures implemented, participant narratives cannot be confidently associated with demographic surveys that hampered the ability to offer an intersectional analysis of participant experience. Originality/value: Discussions of relationship maintenance and digital intimacies elucidate the limitations of health education's tendency to construct adolescent relationships as existing along binaries of "healthy" and "unhealthy." Health education might benefit from more meaningful integration of these concepts.